Assessment of the impact of a twin industrial area on the air quality in Bandar Baru Bangi, Selangor - Mastura Mahmud,; Muhammad Hafiz, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The rapid industrial development in an equatorial developing country poses a dilemma where sustainable and human development should be dynamically balanced in an otherwise interdependent ecosystem. The impact of the presence of two industrial designated areas on the air quality of the surrounding residents in a satellite town of Bandar Baru Bangi (BBB), in the state of Selangor in Peninsular Malaysia was investigated by selecting four air quality sampling stations at the Selaman Industrial Park (SIP), the Bangi Industrial Estate (BIE) and two nearby BBB residential areas. Air quality samplings for particulates of aerodynamic diameter of 10 microns (PM10) and gases such as carbon monoxide (CO) and nitrogen dioxide (NO2) were conducted. ANOVA analysis showed that the concentrations between the four stations were different, where higher daily average concentrations for all air parameters exist at the BIE. The PM10 and CO concentrations were below the New Malaysia Ambient Air Quality Standard (2020) (NMAAQS) unlike the NO2 concentrations at both the industrial parks that exceeded the NMAAQS (2020) of 0.15 ppm. The HYSPLIT modelled air trajectory analysis indicated that weak wind velocities during the southwest monsoon over Malaysia dispersed the pollutants from the industrial areas. The predicted dispersion from the HYSPLIT model simulated different plume patterns for the five days from the two industrial areas due to different wind regime of the day during the southwest monsoon. The results emphasize the importance of good proper urban planning particularly for the placement of industrial areas within a township.